Artificial Intelligence for Dummies - Mueller, John, 1958-; Massaron, Luca (Hoboken, NJ : John Wiley & Sons, Inc., 2022)
"Every time you use a smart device or some sort of slick technology--be it a smartwatch, smart speaker, security alarm, or even customer service chat box--you're engaging with artificial intelligence (AI). If you're curious about how AI is developed--or question whether AI is real--Artificial Intelligence For Dummies holds the answers you're looking for. Starting with a basic definition of AI and explanations of data use, algorithms, special hardware, and more, this reference simplifies this complex topic for anyone who wants to understand what operates the devices we can't live without." --.
Introducing AI -- Defining the role of data -- Considering the use of algorithms -- Pioneering specialized hardware -- Seeing AI uses in computer applications -- Automating common processes -- Using AI the address medical needs -- Relying on AI to improve human interaction -- Performing data analysis for AI -- Employing machine learning in AI -- Improving AI with deep learning -- Developing robots -- Flying with drones -- Utilizing the AI-driven car -- Understanding the nonstarter application -- Seeing AI in space -- Engaging in human endeavors -- Ten occupational categories that AI can't replace -- Ten substantial contributions of AI to society -- Ten ways in which AI has failed.
Includes index.
new book 2023 fall.
Keywords: Artificial intelligence